Innovation and sustainability in the construction industry: a teaching exercise in the University of Brasilia’s Postgraduate Programme in Architecture and Urbanism - Blumenschein, Raquel Naves; Miller, Katia Broeto; Tomé, Maria Ferrari (Revista Brasileira de Pós-Graduação, 2014)
This paper sets out the results of the development of Cais – Conceptionand Analysis in Innovation and Sustainability –, a tool to organisethe reasoning and analysis of projects, designed and used in the discipline “Specials Studies in Technology 1: Innovation and Sustainability in the Construction Industry” in the University of Brasilia’s Postgraduate Programme in Architecture and Urbanism (PPG-FAU/UnB). The method used was divided into grounding, design, analysis and applicability test.The tool improved the organisation and delimitation of research projects, and enabled the analysis of research contributions to innovation and sustainability in the context of the CIPC. It also helped identify paths to communicate research results. This tool can serve as a device to evaluate, leverage and encourage projects that generate results in synergy with innovation and sustainability in the construction industry.